Cobalt carbonate and its preparation method and use

By preparing the core-shell structure of aluminum doped cobalt carbonate in stages, combined with the gradient changes in the morphological structure, the problems of aluminum segregation and material stability are solved, and high electrochemical performance and high voltage are achieved.

CN116062801BActive Publication Date: 2025-04-29JINGMEN GEM NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310255919.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-16
Publication Date
2025-04-29
Estimated Expiration
2043-03-16

AI Technical Summary

Technical Problem

The prior art is difficult to effectively suppress the segregation of aluminum in cobalt carbonate in aluminum doped with high aluminum doped amounts, resulting in a decrease in the electrochemical performance of the material, and the aluminum distribution during the preparation process is uneven, affecting the stability of the material.

Method used

Through the staged preparation method, the core-shell structure of cobalt carbonate is realized, and the doping amount of aluminum is gradually increased from the core to the surface, and the material morphology gradually changes from the core to the surface by adjusting the reaction conditions, forming a block, sheet-like and tight sheet-like hierarchical structure to inhibit aluminum segregation.

Benefits of technology

It effectively suppresses segregation of aluminum, improves the cycling and rate performance of the material, ensures high voltage while reducing capacity loss, and provides a precursor material with excellent performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116062801B_ABST
    Figure CN116062801B_ABST
Patent Text Reader

Abstract

The present invention provides a cobalt carbonate and a preparation method and use thereof. The preparation method comprises the following steps: adding a first cobalt aluminum mixed salt solution and a precipitant solution to a bottom liquid in parallel to perform a first coprecipitation reaction, after reaching a first target particle size, replacing the first cobalt aluminum mixed salt solution with a second cobalt aluminum mixed salt solution, and performing a second coprecipitation reaction with a precipitant solution, after reaching a second target particle size, replacing the second cobalt aluminum mixed salt solution with a third cobalt aluminum mixed salt solution, and performing a third coprecipitation reaction with a precipitant solution to obtain the cobalt carbonate; wherein the mass concentration of aluminum in the first cobalt aluminum mixed salt solution, the second cobalt aluminum mixed salt solution, and the third cobalt aluminum mixed salt solution increases in sequence. The present invention prepares aluminum-doped cobalt carbonate with a core-shell structure in which the aluminum doping amount increases from the inside to the outside, regulates the step distribution of the cobalt carbonate morphology, effectively suppresses the segregation of Al in the aluminum-doped cobalt carbonate, and obtains a lithium cobaltate precursor with excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to cobalt carbonate and a preparation method and application thereof. Background Art

[0002] With the rapid development of the battery industry, Al is a common doping element for LCO modification in the industry. After a large number of scientific research tests, it was found that doping Al has the following advantages: 1. Al has no electrochemical activity under the electrochemical window of LCO, so it is a very stable doping element that can effectively improve the thermal stability and cycle performance of the material; 2. Al 3+ (53.5pm) and Co 3+ (54.5pm) The radius is similar, so it is easy to be incorporated into the unit cell without affecting the structure; 3. As the third most abundant element in the earth's crust, its reserves are abundant and the price is cheap; 4. The Al-O bond strength is higher than the Co-O bond. During the charge and discharge process of LCO, the lattice size of the material becomes smaller, thereby increasing the operating voltage of the battery.

[0003] However, for conventional single-morphology aluminum-doped cobalt carbonate, when Al doping reaches a certain value, excessive aluminum doping will cause the capacitance of LCO to decrease, which is not worth the cost.

[0004] CN108649219 discloses a method for preparing large-particle aluminum-doped cobalt tetroxide, which adopts a semi-continuous process with high working efficiency, but the aluminum doping amount is relatively low and cannot meet the requirements of high voltage, and no good solution is proposed for high aluminum doping.

[0005] Although the concentration method can achieve a higher aluminum doping level, when using the concentration method to prepare cobalt carbonate, the stability of the reaction system will be impacted before and after entering the concentrator, causing local instability. Once aluminum is unevenly distributed, it will affect the subsequent aluminum distribution. This series of phenomena will eventually lead to uneven aluminum distribution within a single particle and uneven aluminum distribution between particles, thereby affecting the electrochemical properties of the material.

[0006] For example, CN108275729A discloses a system and method for preparing cobalt carbonate, the system comprises an overflow trough connected to a reactor, the overflow port of the overflow trough is connected to a thickening inlet of a concentrator; the overflow port of the overflow trough is connected to a feed inlet of the reactor, and the thickening outlet of the concentrator is connected to a feed inlet of the reactor; the method comprises the following steps: the product at the bottom of the reactor is discharged from a discharge port at the bottom of the reactor; the material at the top of the reactor overflows from an overflow port of the reactor at the top of the reactor, and after sedimentation in the overflow trough and / or thickening in the concentrator, returns to the reactor to continue to participate in the reaction. The thickening method is used throughout the preparation of cobalt carbonate in this document, which will result in uneven distribution of aluminum.

[0007] Therefore, how to inhibit the segregation of aluminum in aluminum-doped cobalt carbonate, take into account both high stability and high specific surface area, and at the same time improve the electrochemical performance when preparing it into lithium cobalt oxide, is a technical problem that needs to be solved urgently. Summary of the invention

[0008] The object of the present invention is to provide a cobalt carbonate and a preparation method and use thereof. The preparation method provided by the present invention prepares aluminum-doped cobalt carbonate with a core-shell structure in stages, with the aluminum doping amount increasing from the inside to the outside, and regulates the step distribution of the cobalt carbonate morphology according to different doping amounts, effectively suppresses the segregation of Al in the aluminum-doped cobalt carbonate, and obtains a lithium cobalt oxide precursor with excellent performance, thereby improving the cycle performance and rate performance of lithium cobalt oxide, ensuring its high voltage while reducing capacity loss.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing cobalt carbonate, the preparation method comprising the following steps:

[0011] adding a first cobalt aluminum mixed salt solution and a precipitant solution to a base solution in parallel to perform a first coprecipitation reaction, after reaching a first target particle size, replacing the first cobalt aluminum mixed salt solution with a second cobalt aluminum mixed salt solution, and performing a second coprecipitation reaction with the precipitant solution, after reaching a second target particle size, replacing the second cobalt aluminum mixed salt solution with a third cobalt aluminum mixed salt solution, and performing a third coprecipitation reaction with the precipitant solution to obtain the cobalt carbonate;

[0012] Among them, the mass concentration of aluminum in the first cobalt-aluminum mixed salt solution, the second cobalt-aluminum mixed salt solution and the third cobalt-aluminum mixed salt solution increases successively.

[0013] The preparation method provided by the present invention realizes the step distribution of Al in cobalt carbonate by changing the aluminum doping amount (i.e., the mass concentration of aluminum) of raw materials in different reaction stages, and gradually increases the Al doping amount from the core to the surface, so that the capacitance of lithium cobalt oxide can be ensured and its cycle stability can be improved; at the same time, the preparation method provided by the present invention makes the cobalt carbonate change its morphology while the Al doping amount changes from the core to the surface, the core with a low Al doping amount is a block morphology with a stable structure, the middle part with a medium Al doping amount is a lamellar morphology that can better provide capacitance (i.e., the middle layer is relatively loose), and the surface layer with a high Al doping amount is a compact lamellar morphology with a stable structure that inhibits Al segregation, and the gradient Al doping can ensure that the lithium carbonate has a high capacity while improving its cycle performance, and at the same time, the core-shell morphology structure of cobalt carbonate can reduce the surface segregation problem of aluminum in the case of high aluminum doping through structural modification, and can also improve the material structure stability, and can also improve the cycle performance and rate performance of lithium cobalt oxide, while ensuring its high voltage, reducing the capacity loss, and providing a precursor with excellent performance for positive electrode material factories.

[0014] In the present invention, cobalt and aluminum are directly added as a mixed salt, which is more conducive to the uniform distribution of Al. If aluminum salt is added separately and the concentration is regulated, it will increase the cost and easily cause cobalt and aluminum phase separation.

[0015] Preferably, the mass concentration of cobalt in the first cobalt-aluminum mixed salt solution is 80-110 g / L, for example, 80 g / L, 90 g / L, 100 g / L or 110 g / L.

[0016] Preferably, the mass concentration of aluminum in the first cobalt-aluminum mixed salt solution is 2 to 5 g / L, for example, 2 g / L, 2.5 g / L, 3 g / L, 3.5 g / L, 4 g / L, 4.5 g / L or 5 g / L.

[0017] Preferably, the feed ratio of the first cobalt-aluminum mixed salt solution to the precipitant solution is 1:(2-4), for example, 1:2, 1:2.5, 1:3, 1:3.5 or 1:4, etc.

[0018] Preferably, the mass concentration of the precipitant is 210-260 g / L, for example, 210 g / L, 220 g / L, 230 g / L, 240 g / L, 250 g / L or 260 g / L.

[0019] Preferably, the pH value during the first coprecipitation reaction is 7-9, for example, 7, 7.3, 7.5, 7.7, 8, 8.3, 8.5, 8.8 or 9.

[0020] Preferably, the temperature during the first coprecipitation reaction is 35-70°C, for example, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C.

[0021] Preferably, the rotation speed during the first coprecipitation reaction is 100-300 r / min, for example, 100 r / min, 150 r / min, 200 r / min, 250 r / min or 300 r / min.

[0022] Preferably, the first target particle size is 5-7 μm, for example, 5 μm, 5.5 μm, 6 μm, 6.5 μm or 7 μm.

[0023] In the present invention, if the first target particle size is too large, the specific surface area of ​​the positive electrode material will be reduced, thereby reducing its capacitance, while if it is too small, the core will be unstable and hollow will be formed during the subsequent sintering process.

[0024] Preferably, the mass concentration of cobalt in the second cobalt-aluminum mixed salt solution is 80-110 g / L, for example, 80 g / L, 90 g / L, 100 g / L or 110 g / L.

[0025] Preferably, the mass concentration of aluminum in the second cobalt-aluminum mixed salt solution is 5 to 9 g / L, for example, 5 g / L, 5.5 g / L, 6 g / L, 6.5 g / L, 7 g / L, 7.5 g / L, 8 g / L, 8.5 g / L or 9 g / L, etc.

[0026] Preferably, the second target particle size is 12-15 μm, for example, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm or 15 μm.

[0027] In the present invention, if the second target particle size is too large, the morphology is prone to Al segregation, while if it is too small or too large, segregation cannot be suppressed and the structural stability of the positive electrode material is reduced.

[0028] Preferably, during the second coprecipitation reaction, the feed amount of the second cobalt-aluminum mixed salt solution and the feed amount of the precipitant solution are increased sequentially at a fixed ratio to reach the target feed amount.

[0029] In the present invention, the first coprecipitation reaction process adopts a conventional feeding method, that is, a conventional feeding process for preparing the inner core, so as to ensure that the cobalt carbonate grows at a fixed growth rate. In the second coprecipitation reaction process, the feed amount of the raw materials is increased successively, so that the morphology of the middle aluminum-doped layer can be regulated, and the middle aluminum-doped layer is more loose. In the third coprecipitation reaction process, the feed amount of the raw materials remains unchanged, that is, a fixed feed amount (not a method of increasing to the target feed amount successively, but a fixed feed amount) is used to obtain an aluminum-doped layer with a tight outermost structure. That is, the feeding method of regulating different stages in the present invention realizes the regulation of the morphology of cobalt carbonate, and obtains particles with a layered core-shell structure and different structures between layers. Combined with the change in the mass concentration of aluminum in the preparation process of the present invention, the layer corresponds to the Al doping amount, which reduces the surface segregation problem of aluminum in the case of high aluminum doping, improves the material structure stability, and improves the cycle performance and rate performance of lithium cobalt oxide. While ensuring its high voltage, the capacity loss is reduced, and a precursor with excellent performance is provided for the positive electrode material factory.

[0030] Preferably, in the process of sequentially increasing, the feed amount is increased once every 4 to 10 hours, for example, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours.

[0031] Preferably, in the process of sequentially increasing, the feed amount increased each time is 1 to 4 L / h, such as 1 L / h, 2 L / h, 3 L / h or 4 L / h.

[0032] In the present invention, if the time is too short, the morphology will be compact and the capacitance will be reduced; if the time is too long, the material will be too loose and the stability of the material structure will be affected; if the feed amount is too much, the balance of the reaction system will be affected; if the feed amount is too little, the reaction time will be prolonged and the efficiency will be affected.

[0033] Preferably, the mass concentration of cobalt in the third cobalt-aluminum mixed salt solution is 80-110 g / L, for example, 80 g / L, 90 g / L, 100 g / L or 110 g / L.

[0034] Preferably, the mass concentration of aluminum in the third cobalt-aluminum mixed salt solution is 10-13 g / L, for example, 10 g / L, 10.5 g / L, 11 g / L, 11.5 g / L, 12 g / L, 12.5 g / L or 13 g / L, etc.

[0035] In the present invention, the mass concentrations of aluminum in the first cobalt-aluminum mixed salt solution, the second cobalt-aluminum mixed salt solution and the third cobalt-aluminum mixed salt solution increase sequentially. Within the above numerical range, it is ensured that the mass concentration of aluminum in the third cobalt-aluminum mixed salt solution is greater than the mass concentration of aluminum in the second cobalt-aluminum mixed salt solution and greater than the mass concentration of aluminum in the first cobalt-aluminum mixed salt solution. Even if there are endpoint values ​​in the numerical range, the regularity of sequential increase must still be ensured.

[0036] Preferably, after the third coprecipitation reaction is completed, the material obtained by the reaction is washed and dried in sequence.

[0037] Preferably, the washing temperature is 50-80°C, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C.

[0038] Preferably, the drying temperature is 50-120°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C.

[0039] As a preferred technical solution, the preparation method comprises the following steps:

[0040] The first cobalt aluminum mixed salt solution and the precipitant solution are added to the bottom liquid in a feed ratio of 1: (2-4), and a first coprecipitation reaction is carried out at 35-70° C. and a rotation speed of 100-300 r / min in an environment with a pH value of 7-9. After reaching a first target particle size of 5-7 μm, the first cobalt aluminum mixed salt solution is replaced with a second cobalt aluminum mixed salt solution, and a second coprecipitation reaction is carried out with the precipitant solution. During the second coprecipitation reaction, the feed amount of the second cobalt aluminum mixed salt solution and the feed amount of the precipitant solution are increased by 1-4 L / h at a fixed ratio every 4-10 hours to the target feed amount. After reaching a second target particle size of 12-15 μm, the second cobalt aluminum mixed salt solution is replaced with a third cobalt aluminum mixed salt solution, and a third coprecipitation reaction is carried out with the precipitant solution, and the solution is washed and dried to obtain the cobalt carbonate;

[0041] Among them, the mass concentration of aluminum in the first cobalt-aluminum mixed salt solution, the second cobalt-aluminum mixed salt solution and the third cobalt-aluminum mixed salt solution increases successively; the mass concentration of aluminum in the first cobalt-aluminum mixed salt solution is 2-5 g / L; the mass concentration of aluminum in the second cobalt-aluminum mixed salt solution is 5-9 g / L; the mass concentration of aluminum in the third cobalt-aluminum mixed salt solution is 10-13 g / L.

[0042] The preparation parameters in the second coprecipitation reaction process and the third coprecipitation reaction process provided by the present invention can be adaptively adjusted according to actual needs based on the parameters of the first coprecipitation reaction.

[0043] In a second aspect, the present invention provides a cobalt carbonate, which is prepared by the method for preparing cobalt carbonate as described in the first aspect, and the cobalt carbonate comprises, from the inside to the outside, an aluminum-doped core, a first aluminum-doped layer, and a second aluminum-doped layer; wherein the doping amounts of aluminum in the aluminum-doped core, the first aluminum-doped layer, and the second aluminum-doped layer increase sequentially.

[0044] Preferably, the compactness of the second Al-doped layer is higher than the compactness of the first Al-doped layer and the compactness of the Al-doped core.

[0045] In the present invention, the compactness of the second aluminum-doped layer is higher than that of the other two layers (the inner core and the first layer in the middle), so that while suppressing Al segregation, the surface structure stability of the lithium cobalt oxide positive electrode material can be enhanced, thereby enhancing its cycle stability.

[0046] The cobalt carbonate provided by the present invention has an aluminum doping amount that increases from the inside to the outside, and at the same time, combined with a special morphology structure, the Al doping amount is gradually increased from the core to the surface, which can ensure the capacitance of LCO and improve its cycle stability. However, when the surface Al doping amount is high, Al is prone to segregation, resulting in uneven Al distribution. By changing the reaction conditions, the morphology of the cobalt carbonate changes from the core to the surface while the Al doping amount changes. The core with a low Al doping amount is a block morphology with a stable structure, the middle part with a medium Al doping amount is a lamellar morphology that can better provide capacitance, and the surface layer with a high Al doping amount is a compact lamellar morphology with a stable structure that suppresses Al segregation. Reducing the surface segregation problem of aluminum in the case of high aluminum doping can improve the structural stability of the material, and can also improve the cycle performance and rate performance of lithium cobalt oxide, providing a precursor with excellent performance for the positive electrode material factory.

[0047] In a third aspect, the present invention provides a lithium cobalt oxide positive electrode material, wherein the lithium cobalt oxide positive electrode material is obtained by mixing and sintering cobalt trioxide and a lithium source; the cobalt trioxide is obtained by calcining the cobalt carbonate described in the second aspect.

[0048] In a fourth aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the lithium cobalt oxide positive electrode material as described in the third aspect.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] The preparation method provided by the present invention realizes the step distribution of Al in cobalt carbonate by changing the Al doping amount (i.e., the mass concentration of aluminum) of the raw materials in different reaction stages, and gradually increases the Al doping amount from the core to the surface, so that the capacitance of lithium cobalt oxide can be guaranteed and its cycle stability can be improved; when the Al doping amount on the surface is high, Al is prone to segregation, resulting in uneven Al distribution. The present invention further changes the reaction conditions so that the Al doping amount of cobalt carbonate changes from the core to the surface, and the morphology also changes accordingly. The core with a low Al doping amount has a block morphology with a stable structure, and the Al doping amount has a block morphology with a stable structure. The middle part with medium Al content is lamellar (i.e., the middle layer is relatively loose) which can provide better capacitance, and the surface layer with higher Al content is a compact lamellar morphology with stable structure that inhibits Al segregation. Gradient Al doping can ensure that lithium carbonate has a higher capacity while improving its cycle performance. At the same time, the core-shell morphology of cobalt carbonate can reduce the surface segregation of aluminum in the case of high Al doping through structural modification, thereby improving the structural stability of the material, and improving the cycle performance and rate performance of lithium cobalt oxide, ensuring its high voltage while reducing capacity loss, providing a precursor with excellent performance for positive electrode material factories. The positive electrode material in the battery is prepared from the precursor material provided by the present invention, and during the preparation process, in the second coprecipitation reaction process, the feeding method of the raw materials is increased successively, and in the third precipitation process, the feed amount is fixed, and the battery capacity under 0.5C / 1C conditions in the voltage range of 2 to 4.65V can reach more than 190mAh / g, the capacity retention rate after 100 cycles can reach more than 90%, and the 0.5C / 2C rate performance can reach more than 79%, thereby achieving an improvement in the comprehensive performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is a SEM image of the aluminum-doped core in the aluminum-doped cobalt carbonate provided in Example 1.

[0052] Figure 2 This is a SEM image of the surface of the first aluminum-doped layer in the aluminum-doped cobalt carbonate provided in Example 1 (particles of the second target particle size).

[0053] Figure 3 This is a SEM image of the surface of the aluminum-doped cobalt carbonate provided in Example 1.

[0054] Figure 4 This is a cross-sectional SEM image of the aluminum-doped cobalt carbonate provided in Example 1.

[0055] Figure 5 This is the energy spectrum of Al in the aluminum-doped cobalt carbonate provided in Example 1. DETAILED DESCRIPTION

[0056] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0057] Example 1

[0058] The present embodiment provides an aluminum-doped cobalt carbonate, which includes an aluminum-doped core, a first aluminum-doped layer, and a second aluminum-doped layer from the inside to the outside; wherein the doping amounts of aluminum in the aluminum-doped core, the first aluminum-doped layer, and the second aluminum-doped layer increase sequentially; the aluminum-doped core has a block-like morphology, the first aluminum-doped layer has a loose lamellar morphology, and the second aluminum-doped layer has a dense lamellar morphology (the density of the second aluminum-doped layer is higher than that of the first aluminum-doped layer and that of the aluminum-doped core).

[0059] The preparation method of the cobalt carbonate is as follows:

[0060] (1) firstly, cobalt sulfate and aluminum sulfate are prepared into solution A (first cobalt-aluminum mixed salt solution) with a Co concentration of 100 g / L and an Al concentration of 3 g / L; solution B (second cobalt-aluminum mixed salt solution) with a Co concentration of 100 g / L and an Al concentration of 7 g / L; solution C (third cobalt-aluminum mixed salt solution) with a Co concentration of 100 g / L and an Al concentration of 11 g / L, and simultaneously 230 g / L of ammonium carbonate solution D (precipitant solution);

[0061] (2) Pure water plus solution D is used as the reaction base liquid, and solution A and solution D are added to the base liquid in parallel at a feed ratio of 1:3, and the pH value is controlled to be 8. The coprecipitation reaction is carried out at a speed of 200 r / min at 45°C. When the reaction particle size reaches 5 μm (core), solution A is replaced by solution B. The feed ratio of solution B and solution D remains unchanged. The feed rate is increased by 5 L / h every 2 h (the second target flow rate value is: 70 L / h), and the pH value is controlled to be 8. The second coprecipitation reaction is carried out at a speed of 200 r / min at 45°C. When the cobalt carbonate particle size is 12 μm, solution B is replaced by solution C, and the third coprecipitation reaction is continued according to the fixed flow rate until the particle size reaches the required value of 19±0.5 μm, and the reactor is stopped;

[0062] (3) When the particle size reaches the stopping particle size, the reacted material is washed with hot water at 60° C., and then dried at 100° C. to obtain the cobalt carbonate.

[0063] Figure 1 The SEM image of the aluminum-doped core in the aluminum-doped cobalt carbonate provided in Example 1 is shown; Figure 2 The SEM image of the surface of the first aluminum-doped layer in the aluminum-doped cobalt carbonate provided in Example 1 (particles of the second target particle size) is shown; Figure 3 The SEM image of the surface of the aluminum-doped cobalt carbonate provided in Example 1 is shown. Figure 1 It can be seen that the core has a blocky morphology (aluminum-doped core). This morphology is suitable for the initial stage of the reaction. While providing a stable core, it can also enable faster nucleation and agglomeration, thus reducing the reaction time. Figure 2 It shows that the second layer is composed of vertical fine lamellar crystals (the first aluminum-doped layer). Such a morphology can provide a larger specific surface area and have a better capacity after being prepared into a battery. Figure 3 The core is tightly wrapped by dense lateral lamellar crystals (the second aluminum-doped layer), and the lateral crystals suppress the segregation of the Al phase. At the same time, this morphology has better structural stability, delays the structural collapse during battery use, and improves the battery's cycle capacity.

[0064] Figure 4 The cross-sectional SEM image of the aluminum-doped cobalt carbonate provided in Example 1 is shown. Figure 4 It can be seen that the synthesized cobalt carbonate is clearly divided into three layers, and the surface is more compact, indicating that the prepared morphology is indeed distributed layer by layer.

[0065] Figure 5 The energy spectrum of Al in the aluminum-doped cobalt carbonate provided in Example 1 is shown. Figure 5 It can be seen that the Al content of the synthesized cobalt carbonate increases gradually from the first layer to the second layer and then to the third layer (i.e., from the inner core to the outermost layer, inner core-first aluminum-doped layer-second aluminum-doped layer), and corresponds one to one with the morphology distribution, proving that the Al doping amount does correspond completely to the morphology.

[0066] Example 2

[0067] The present embodiment provides an aluminum-doped cobalt carbonate, which includes an aluminum-doped core, a first aluminum-doped layer, and a second aluminum-doped layer from the inside to the outside; wherein the doping amounts of aluminum in the aluminum-doped core, the first aluminum-doped layer, and the second aluminum-doped layer increase sequentially; the aluminum-doped core has a block-like morphology, the first aluminum-doped layer has a loose lamellar morphology, and the second aluminum-doped layer has a dense lamellar morphology (the density of the second aluminum-doped layer is higher than that of the first aluminum-doped layer and that of the aluminum-doped core).

[0068] The preparation method of the cobalt carbonate is as follows:

[0069] (1) firstly, cobalt nitrate and aluminum nitrate are prepared into solution A (first cobalt-aluminum mixed salt solution) with a Co concentration of 80 g / L and an Al concentration of 2 g / L; solution B (second cobalt-aluminum mixed salt solution) with a Co concentration of 80 g / L and an Al concentration of 5 g / L; solution C (third cobalt-aluminum mixed salt solution) with a Co concentration of 80 g / L and an Al concentration of 10 g / L, and at the same time, 210 g / L of ammonium carbonate solution D (precipitant solution) is prepared;

[0070] (2) Pure water plus solution D is used as the reaction base liquid, and solution A and solution D are added to the base liquid in parallel at a feed ratio of 1:2, and the pH value is controlled to be 7.5. The coprecipitation reaction is carried out at a speed of 200 r / min at 50°C. When the reaction particle size reaches 6 μm (core), solution A is replaced by solution B, and the feed ratio of solution B to solution D remains unchanged. The feed rate is increased by 1 L / h every 1 h (the second target flow value is: 70 L / h), and the pH value is controlled to be 7.5. The second coprecipitation reaction is carried out at a speed of 150 r / min at 40°C. When the cobalt carbonate particle size is 13.5 μm, solution B is replaced by solution C, and the third coprecipitation reaction is continued according to the fixed flow rate until the particle size reaches the required value of 19±0.5 μm, and the reactor is stopped;

[0071] (3) When the particle size reaches the stopping particle size, the reacted material is washed with hot water at 60° C., and then dried at 100° C. to obtain the cobalt carbonate.

[0072] Example 3

[0073] The present embodiment provides an aluminum-doped cobalt carbonate, which includes an aluminum-doped core, a first aluminum-doped layer, and a second aluminum-doped layer from the inside to the outside; wherein the doping amounts of aluminum in the aluminum-doped core, the first aluminum-doped layer, and the second aluminum-doped layer increase sequentially; the aluminum-doped core has a block-like morphology, the first aluminum-doped layer has a loose lamellar morphology, and the second aluminum-doped layer has a dense lamellar morphology (the density of the second aluminum-doped layer is higher than that of the first aluminum-doped layer and that of the aluminum-doped core).

[0074] The preparation method of the cobalt carbonate is as follows:

[0075] (1) firstly, cobalt sulfate and aluminum sulfate are prepared into solution A (first cobalt-aluminum mixed salt solution) with a Co concentration of 110 g / L and an Al concentration of 5 g / L; solution B (second cobalt-aluminum mixed salt solution) with a Co concentration of 110 g / L and an Al concentration of 9 g / L; solution C (third cobalt-aluminum mixed salt solution) with a Co concentration of 110 g / L and an Al concentration of 13 g / L, and simultaneously 230 g / L of ammonium carbonate solution D (precipitant solution);

[0076] (2) Pure water and solution D are used as the reaction base liquid, and solution A and solution D are added to the base liquid in parallel at a feed ratio of 1:4, and the pH value is controlled to be 8. The coprecipitation reaction is carried out at a speed of 200 r / min at 45°C. When the reaction particle size reaches 7 μm (core), solution A is replaced by solution B. The feed ratio of solution B and solution D remains unchanged. The feed rate is increased by 10 L / h every 4 h (the second target flow rate value is: 70 L / h), and the pH value is controlled to be 8. The second coprecipitation reaction is carried out at a speed of 200 r / min at 45°C. When the cobalt carbonate particle size is 15 μm, solution B is replaced by solution C, and the third coprecipitation reaction is continued according to the fixed flow rate until the particle size reaches the required value of 19±0.5 μm, and the reactor is stopped;

[0077] (3) When the particle size reaches the stopping particle size, the reacted material is washed with hot water at 60° C., and then dried at 100° C. to obtain the cobalt carbonate.

[0078] Example 4

[0079] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, after solution A is replaced by solution B, the feed is directly fed at a fixed feed rate (without the process of increasing the feed rate).

[0080] The rest of the preparation methods and parameters were the same as those in Example 1.

[0081] Example 5

[0082] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, after solution B is replaced by solution C, the feeding rule is consistent with that in the second coprecipitation reaction process.

[0083] The rest of the preparation methods and parameters were the same as those in Example 1.

[0084] Comparative Example 1

[0085] The difference between this comparative example and Example 1 is that the concentration of aluminum in the cobalt-aluminum mixed salt solution in this comparative example is consistently 11 g / L, and no staged preparation is performed during the preparation process (preparation is performed according to the parameters of the first stage), i.e., aluminum-doped cobalt carbonate with a core-shell structure is not prepared.

[0086] The rest of the preparation methods and parameters were the same as those in Example 1.

[0087] The cobalt carbonate provided in Examples 1-5 and Comparative Example 1 was calcined at 500° C. for 3 h to obtain aluminum-doped cobalt oxide, and the aluminum-doped cobalt oxide was mixed with lithium hydroxide and sintered to obtain a lithium cobalt oxide positive electrode material.

[0088] The lithium cobalt oxide positive electrode materials provided in Examples 1-5 and Comparative Example 1 were used to prepare positive electrode sheets, and the metal lithium sheet was used as the negative electrode. The button-type battery was assembled for charge and discharge tests. The battery capacity, 100 cycle capacity retention rate, and 0.5C / 2C capacity retention rate were tested under a high voltage range of 2 to 4.65V and then under 0.5C / 1C conditions. The test results are shown in Table 1.

[0089] Table 1

[0090]

[0091] It can be seen from the data results of Example 1 and Example 4 that during the second co-precipitation reaction, the feeding method of the raw materials is not to increase sequentially, but to feed at a fixed feeding amount, which is not conducive to maintaining the morphology, affects the specific surface area of ​​the positive electrode material, and thus reduces the capacity of the battery.

[0092] It can be seen from the data results of Example 1 and Example 5 that during the third co-precipitation reaction, if the raw material is not fed in a fixed amount, the battery cycle capacity retention rate will be seriously reduced.

[0093] It can be seen from the data results of Example 1 and Comparative Example 1 that in the case of high aluminum doping, the single morphology of cobalt carbonate material will seriously affect the capacity of the battery, and while increasing the cycle rate, the capacity of the battery is seriously sacrificed.

[0094] In summary, the preparation method provided by the present invention realizes the step distribution of Al in cobalt carbonate by changing the Al doping amount (i.e., the mass concentration of aluminum) of the raw materials in different reaction stages, and gradually increases the Al doping amount from the core to the surface, which can ensure the capacitance of lithium cobalt oxide and improve its cycle stability; when the Al doping amount on the surface is high, Al is prone to segregation, resulting in uneven Al distribution. The present invention further changes the reaction conditions so that the Al doping amount of cobalt carbonate changes from the core to the surface, and the morphology also changes accordingly. The core with a low Al doping amount has a stable block morphology, and the doped The middle part with medium Al content is a lamellar shape that can better provide capacitance (i.e., the middle layer is relatively loose), and the surface layer with a high Al content is a compact lamellar morphology with a stable structure that inhibits Al segregation. Gradient Al doping can ensure that lithium carbonate has a high capacity while improving its cycle performance. At the same time, the core-shell morphology structure of cobalt carbonate reduces the surface segregation problem of aluminum under high aluminum doping through structural modification, and can improve the structural stability of the material, and can also improve the cycle performance and rate performance of lithium cobalt oxide, while ensuring its high voltage, reducing capacity loss, and providing a precursor with excellent performance for the positive electrode material factory. The positive electrode material in the battery is prepared from the precursor material provided by the present invention, and in the preparation process, during the second coprecipitation reaction process, the feeding method of the raw materials is successively increased, and during the third precipitation process, the feed is fed with a fixed feed amount, the capacity of the battery under the condition of 0.5C / 1C can reach more than 190mAh / g, the capacity retention rate after 100 cycles can reach more than 90%, and the rate performance of 0.5C / 2C can reach more than 79%, realizing the improvement of the comprehensive performance of the material.

[0095] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing cobalt carbonate, characterized in that: The preparation method comprises the following steps: adding a first cobalt aluminum mixed salt solution and a precipitant solution to a base solution in parallel to perform a first coprecipitation reaction, after reaching a first target particle size, replacing the first cobalt aluminum mixed salt solution with a second cobalt aluminum mixed salt solution, and performing a second coprecipitation reaction with the precipitant solution, after reaching a second target particle size, replacing the second cobalt aluminum mixed salt solution with a third cobalt aluminum mixed salt solution, and performing a third coprecipitation reaction with the precipitant solution to obtain the cobalt carbonate; The mass concentration of aluminum in the first cobalt-aluminum mixed salt solution, the second cobalt-aluminum mixed salt solution and the third cobalt-aluminum mixed salt solution increases in sequence; During the second coprecipitation reaction, the feed amount of the second cobalt-aluminum mixed salt solution and the feed amount of the precipitant solution are increased sequentially at a fixed ratio to reach the target feed amount.

2. The method for preparing cobalt carbonate according to claim 1, characterized in that The mass concentration of cobalt in the first cobalt-aluminum mixed salt solution is 80-110 g / L.

3. The method for preparing cobalt carbonate according to claim 1, characterized in that The mass concentration of aluminum in the first cobalt-aluminum mixed salt solution is 2-5 g / L.

4. The method for preparing cobalt carbonate according to claim 1, characterized in that The feed ratio of the first cobalt-aluminum mixed salt solution to the precipitant solution is 1:(2-4).

5. The method for preparing cobalt carbonate according to claim 1, characterized in that: The mass concentration of the precipitant is 210-260 g / L.

6. The method for preparing cobalt carbonate according to claim 1, characterized in that: The pH value during the first coprecipitation reaction is 7-9.

7. The method for preparing cobalt carbonate according to claim 1, characterized in that: The temperature during the first coprecipitation reaction is 35-70°C.

8. The method for preparing cobalt carbonate according to claim 1, characterized in that: The rotation speed during the first coprecipitation reaction is 100-300 r / min.

9. The method for preparing cobalt carbonate according to claim 1, characterized in that: The first target particle size is 5-7 μm.

10. The method for preparing cobalt carbonate according to claim 1, characterized in that: The mass concentration of cobalt in the second cobalt-aluminum mixed salt solution is 80-110 g / L.

11. The method for preparing cobalt carbonate according to claim 1, characterized in that: The mass concentration of aluminum in the second cobalt-aluminum mixed salt solution is 5 to 9 g / L.

12. The method for preparing cobalt carbonate according to claim 1, characterized in that: The second target particle size is 12-15 μm.

13. The method for preparing cobalt carbonate according to claim 1, characterized in that: During the sequential increasing process, the feed amount is increased every 4 to 10 hours.

14. The method for preparing cobalt carbonate according to claim 1, characterized in that: During the sequential increasing process, the feed amount increased each time is 1 to 4 L / h.

15. The method for preparing cobalt carbonate according to claim 1, characterized in that: The mass concentration of cobalt in the third cobalt-aluminum mixed salt solution is 80-110 g / L.

16. The method for preparing cobalt carbonate according to claim 1, characterized in that: The mass concentration of aluminum in the third cobalt-aluminum mixed salt solution is 10-13 g / L.

17. The method for preparing cobalt carbonate according to claim 1, characterized in that: After the third coprecipitation reaction is completed, the material obtained by the reaction is washed and dried in sequence.

18. The method for preparing cobalt carbonate according to claim 17, characterized in that: The washing temperature is 50-80°C.

19. The method for preparing cobalt carbonate according to claim 17, characterized in that: The drying temperature is 50-120°C.

20. The method for preparing cobalt carbonate according to claim 1, characterized in that: The preparation method comprises the following steps: The first cobalt aluminum mixed salt solution and the precipitant solution are added to the bottom liquid in a feed ratio of 1: (2-4), and a first coprecipitation reaction is carried out at 35-70° C. and a rotation speed of 100-300 r / min in an environment with a pH value of 7-9. After reaching a first target particle size of 5-7 μm, the first cobalt aluminum mixed salt solution is replaced with a second cobalt aluminum mixed salt solution, and a second coprecipitation reaction is carried out with the precipitant solution. During the second coprecipitation reaction, the feed amount of the second cobalt aluminum mixed salt solution and the feed amount of the precipitant solution are increased by 1-4 L / h at a fixed ratio every 4-10 hours to the target feed amount. After reaching a second target particle size of 12-15 μm, the second cobalt aluminum mixed salt solution is replaced with a third cobalt aluminum mixed salt solution, and a third coprecipitation reaction is carried out with the precipitant solution, and the solution is washed and dried to obtain the cobalt carbonate; Among them, the mass concentration of aluminum in the first cobalt-aluminum mixed salt solution, the second cobalt-aluminum mixed salt solution and the third cobalt-aluminum mixed salt solution increases successively; the mass concentration of aluminum in the first cobalt-aluminum mixed salt solution is 2-5 g / L; the mass concentration of aluminum in the second cobalt-aluminum mixed salt solution is 5-9 g / L; the mass concentration of aluminum in the third cobalt-aluminum mixed salt solution is 10-13 g / L.

21. A cobalt carbonate, characterized in that The cobalt carbonate is prepared by the method for preparing cobalt carbonate according to any one of claims 1 to 20, and the cobalt carbonate comprises, from the inside to the outside, an aluminum-doped core, a first aluminum-doped layer, and a second aluminum-doped layer; wherein the doping amounts of aluminum in the aluminum-doped core, the first aluminum-doped layer, and the second aluminum-doped layer increase sequentially.

22. The cobalt carbonate according to claim 21, characterized in that The compactness of the second Al-doped layer is higher than the compactness of the first Al-doped layer and the compactness of the Al-doped core.

23. A lithium cobalt oxide positive electrode material, characterized in that: The lithium cobalt oxide positive electrode material is obtained by mixing cobalt tetroxide and a lithium source and sintering them; the cobalt tetroxide is obtained by calcining the cobalt carbonate as claimed in claim 21 or 22.

24. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium cobalt oxide positive electrode material as claimed in claim 23.

Citation Information

Patent Citations

  • System and method for preparing cobalt carbonate

    CN108275729A

  • Multilayer core-shell structure aluminum-doped cobaltosic oxide and preparation method thereof

    CN112125350A

  • Al gradient type doped lithium cobalt oxide positive electrode material and preparation method thereof

    CN115676902A